Online Flipped Classroom in Electricity and Magnetism Course Supported Google Classroom and Telegram: A Case Study - Furqon, M (Education and Talent Development Center Indonesia (ETDC Indonesia), 2024)
The online flipped classroom is a learning design gaining popularity in the current Education 4.0 era. This learning design combines the synchronous and asynchronous learning and provides opportunities for students to explore material before virtual meetings and solve problems directly during virtual meetings. This study aims to obtain an overview of the online flipped classroom implementation in physics courses. The researcher used the qualitative method in this study. Data collection was carried out through observation and documentation toward two lecturers and 25 physics education students taking electricity and magnetism courses at a university in West Java. The results showed that electricity and magnetism online learning combined asynchronous and synchronous learning through Google Classroom and Telegram in three stages: pre-class, in-class, and post-class. Studies on online learning using other learning management systems and social media to gain a more comprehensive overview of the use of learning management systems and social media in online learning are suggested.